2019
DOI: 10.1186/s12889-019-7580-9
|View full text |Cite
|
Sign up to set email alerts
|

Holding the keys to health? A scoping study of the population health impacts of automated vehicles

Abstract: Background Automated Vehicles (AVs) are central to the new mobility paradigm that promises to transform transportation systems and cities across the globe. To date, much of the research on AVs has focused on technological advancements with little emphasis on how this emerging technology will impact population-level health. This scoping study examines the potential health impacts of AVs based on the existing literature. Methods Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 52 publications
0
23
0
1
Order By: Relevance
“…But it is clear that there is a broad range of potential positive impacts of automated vehicle technology in the lives of older adults. Even more broadly it can help bridge disparities in social and environmental determinants associated with health[ 93 ].…”
Section: Driverless Vehiclesmentioning
confidence: 99%
“…But it is clear that there is a broad range of potential positive impacts of automated vehicle technology in the lives of older adults. Even more broadly it can help bridge disparities in social and environmental determinants associated with health[ 93 ].…”
Section: Driverless Vehiclesmentioning
confidence: 99%
“…A scoping review can be used to inform readers of the current state of evidence for an area of practice (or an emerging topic) or to provide direction for future research priorities (Colquhoun et al, ; Peterson, Pearce, Ferguson, & Langford, ). Scoping reviews have also been used to identify social determinants of health, as well as highlight strengths and weaknesses in fields of research (Dean et al, ; Yii, Palermo, & Kleve, ). To summarize, the rationales which best suit a scoping review are exploratory in nature, for example, scoping a field in order to identify future systematic review topics, to identify gaps in the research literature, to map concepts or definitions related to a research area, or clarify conceptual parameters, or to provide a summative overview of a topic, field of inquiry or concept (Colquhoun et al, ; Cooper et al, ; Peters et al, ; Tricco et al, ).…”
Section: What a Scoping Review Is (And What They Are Useful For)mentioning
confidence: 99%
“…Are automated vehicles (AVs) the panacea that some seem to think? A recent review proposed a range of impacts on health: reducing injuries was paramount, with effects on air quality, physical activity, and stress being less certain (Dean et al, 2019). However, a study in the USA found that the number of pedestrians that could be detected by an AV prior to a fatal collision ranged from below 30% to above 90%, a range that is not reassuring (Combs et al, 2019).…”
Section: Automated Vehiclesmentioning
confidence: 99%